2021
DOI: 10.1002/jmrs.540
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of patient selection methods for proton therapy

Abstract: The aim was to explore various national and international clinical decisionmaking tools and dose comparison methods used for selecting cancer patients for proton versus X-ray radiation therapy. To address this aim, a literature search using defined scoping review methods was performed in Medline and Embase databases as well as grey literature. Articles published between 1 January 2015 and 4 August 2020 and those that clearly stated methods of proton versus X-ray therapy patient selection and those published in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
(169 reference statements)
0
5
0
Order By: Relevance
“…It is clear that some cancer sites may benefit more than others from the advantages proton treatment can offer [6]. Treatment sites where the benefit of protons was sufficiently shown have become standard indications in many countries [7][8][9]. However, for some treatment sites the benefit is more heterogeneous and the magnitude of the advantage regarding toxicity reduction is highly dependent on individual patient factors and dose distributions.…”
mentioning
confidence: 99%
“…It is clear that some cancer sites may benefit more than others from the advantages proton treatment can offer [6]. Treatment sites where the benefit of protons was sufficiently shown have become standard indications in many countries [7][8][9]. However, for some treatment sites the benefit is more heterogeneous and the magnitude of the advantage regarding toxicity reduction is highly dependent on individual patient factors and dose distributions.…”
mentioning
confidence: 99%
“…In the US, the number of cases treated with PT increased from 0.4% in 2004 to 1.2% in 2018 (annual percent change [APC], 8.12%; P <.001) [12] . Of note, criteria to indicate PT among different nations remain very heterogenous and are based on different parameters such as reimbursement, literature evidence or technical aspects [6] , [16] , [20] . A recent survey showed that 4233 adult patients have been treated in 2020 in 19 European PT centers [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric cancer is the most common indication for PT as concerns related to long-term side effects in surviving patients. Indeed, a scoping review revealed that PT was indicated for a majority of benign and malignant pediatric tumours, with consensus across the investigated nations (United Kingdom, USA, Canada, Nederland, Australia and New Zealand) for the following tumors: base of skull and spinal chordomas and chondrosarcomas, intracranial germ cell tumors, rhabdomyosarcoma, Ewing sarcoma, optic pathways, and other low-grade gliomas and craniopharyngiomas [20] . A large-scale analysis conducted using the American National Cancer Database (NCDB) assessed that the overall proportion of pediatric (<21 years) patients treated with PT between 2004 and 2013 increased from 1.7 to 17.5% [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Additional normal tissue control probability and toxicity risk reduction models have been described [19,20]. In a scoping review of patient selection models for proton therapy in head and neck cancers, Zientara et al [21] reported a few methods including but not limited to informed decision-making, cost effectiveness, normal tissue complication probability comparisons between plans, prediction software comparing doses to the tumor volume and organs at risk, and multidisciplinary team consensus. In addition to these selection models, patients should optimally be enrolled into clinical trials comparing protons to photons.…”
Section: Discussionmentioning
confidence: 99%